(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
In primary education, enhancing student engagement in the learning process, reinforcing knowledge, and fostering creative thinking are among the key objectives of effective pedagogical approaches. To achieve these goals, didactic games are increasingly used as an effective tool in educational practice. A didactic game is considered an interactive method that serves to develop students’ knowledge, skills, and competencies through game elements. This article provides information on these aspects and discusses their pedagogical significance.